Aortic Augmentation Index Is Inversely Associated With Cardiorespiratory Fitness in Men Without Known Coronary Heart Disease - Binder, Josepha; Bailey, Kent R.; Seward, James B.; Squires, Ray W.; Kunihiro, Takamu; Hensrud, Donald D.; Kullo, Iftikhar J. (American journal of hypertension, 2006)
We investigated whether the aortic augmentation index (AIx), a measure of arterial wave reflection and stiffness, is associated with cardiorespiratory fitness in men without known coronary heart disease (CHD). Asymptomatic men ( n = 201, mean age 51 ± 9.2 years) referred for a screening exercise electrocardiogram (ECG) underwent applanation tonometry to obtain radial artery pulse waveforms, and an ascending aortic pressure waveform was derived by a transfer function. The AIx is the difference between the first and second systolic peak of the ascending aortic pressure waveform, expressed as a percentage of the pulse pressure. Cardiorespiratory fitness was assessed by maximal oxygen consumption (VO 2 max mL/min/kg) during a symptom-limited graded exercise test. Multivariable regression analyses were used to identify significant independent determinants of AIx and of VO 2 max. Diabetes was present in 2.5% of subjects, 34.8% had history of smoking, and 29% were hypertensive. Mean (± SD) AIx was 19.9% ± 9.0% and mean VO 2 max was 33.9 ± 6.4 mL/min/kg. In a multivariable linear regression model, AIx was positively associated with age, hypertension, and history of smoking and inversely with heart rate, height, and body mass index (BMI). The VO 2 max was significantly inversely related to AIx after adjustment for age, heart rate, height, and BMI ( r = −0.22, P = .002), after further adjustment for CHD risk factors (total cholesterol, HDL-cholesterol, history of smoking, diabetes, hypertension) ( P = .006), and after additional adjustment for behavioral factors (physical activity score, alcohol intake, and percent body fat) ( P = .022). These findings indicate that AIx, a measure of arterial wave reflection and stiffness, is inversely associated with cardiorespiratory fitness in men without CHD.